2019
DOI: 10.1021/acs.cgd.9b00966
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Mediated Mineralization of TiO2 Nanotubes Subjected to Different Heat Treatments

Abstract: Surface-modified titanium (Ti) and titanium alloys with physical topography and bioactive components mimicking those of bone tissues have attracted increasing interest as biomaterials for accelerating osseointegration. In this study, an enzyme-mediated mineralization system containing an organic phosphate is used to form a coating of calcium phosphate on titanium dioxide (TiO 2 ) nanotubes heat-treated at different temperatures (350, 450, and 550 °C). Surface characterization using analytical techniques shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Moreover, MEM used in this study contained several enzymes, such as alkaline phosphatase. Previous study suggested that this enzyme may slow down the formation of HA [41] and stabilize the minerals in the precursor phases, such as ACP or OCP. However, HEPES in SHARP solution could keep the pH stable at 7.4 as seen from Figure 4.…”
Section: Calcium Phosphate (Cap) Formation In the Different Immersion...mentioning
confidence: 99%
“…Moreover, MEM used in this study contained several enzymes, such as alkaline phosphatase. Previous study suggested that this enzyme may slow down the formation of HA [41] and stabilize the minerals in the precursor phases, such as ACP or OCP. However, HEPES in SHARP solution could keep the pH stable at 7.4 as seen from Figure 4.…”
Section: Calcium Phosphate (Cap) Formation In the Different Immersion...mentioning
confidence: 99%
“…Yun et al used an enzyme-mediated mineralization system to form a calcium phosphate (CaP) coating on a titanium modified surface annealed at high temperature. 126 The combination of the TNT's nanotopography as a physical cue and a bioactive CaP layer as a chemical cue endowed synergistically improved preosteoblast proliferation and differentiation in comparison to surfaces with only TNT topography or CaP coating. Bartkowiak et al reported that surface functionalization with an HA coating improved the performance of current titanium-based implants.…”
Section: Tio 2 In Bone Tissue Regenerationmentioning
confidence: 99%